Sun safety in construction: a profiling and intervention study - Madgwick, Paul. M. (2016)
Background: Construction workers spend a large proportion of their work time outdoors, placing them at increased risk for skin cancer. To date, no large-scale studies have examined occupational sun safety knowledge, attitudes, and practices within this group in the UK context. Given the high incidence of skin cancer attributable to sun exposure in construction relative to other occupational groups, interventions to promote sun safety in the UK construction sector are warranted.